Penerapan Media Wordwall Untuk Meningkatkan Hasil Belajar Pada Materi Notice - Amin, Wahyuni (Indonesian Journal of Pedagogical and Social Sciences, 2024)
Abstract. Technology is growing and becoming the most influential thing in the life of every human being and cannot be denied anymore. One of the things that contributes to the impact of increasingly sophisticated technology is education. In the era of increasingly advanced information and communication technology, the use of digital learning media is an attractive alternative to improve student learning outcomes. One of the digital learning media that can be used is Wordwall. Wordwall is an online learning platform that provides a variety of interactive activities such as flashcards, quizzes and word games. This research was conducted using the method of classroom action research (CAR). Data collection was obtained through test methods, observation guides and interviews. Analysis of test results showed that students experienced a consistent increase in learning outcomes in both cycles when compared to learning outcomes during the preliminary study. The success criteria can also be seen from the results of implementing Actions in both cycles. Supporting data through observation also shows that the use of wordwall media can improve student learning outcomes. Keywords: Learning outcomes; Wordwall web media; Notice